1998
DOI: 10.1136/jnnp.64.3.325
|View full text |Cite
|
Sign up to set email alerts
|

Decreased driving ability in people with Parkinson's disease

Abstract: Background-Driving is a complex form of activity involving especially cognitive and psychomotor functions. These functions may be impaired by Parkinson's disease. The relation between Parkinson's disease and driving ability is still obscure and clinicians have to make decisions concerning the driving ability of their patients based on insuYcent information. Until now no studies have compared diVerent methods for evaluating the driving ability of patients with Parkinson's disease. Methods-The driving ability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
182
6
15

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(221 citation statements)
references
References 29 publications
17
182
6
15
Order By: Relevance
“…Consistent with these latter findings, Madeley et al (1990) found a correlation between PD severity on Webster's rating scale (a 10 item scale of Parkinsonian motor symptoms) and simulated driving reaction time and steering accuracy, and Radford et al (2004) found that the Webster's rating scale, but not cognitive measures, differentiated between safe and unsafe driving on a road test. On the other hand, two more recent studies found that (1) on-road driving performance in PD patients was related to visual processing speed, levodopa dosage, and age, rather than to the Webster's scale (Heikkila et al, 1998); and (2) that although PD drivers were less safe compared to controls on a road test, standard clinical disease markers (i.e., H&Y, UPDRS) did not reliably predict driving performance, suggesting that other measures are necessary to predict driving safety in PD (Wood et al, 2005). In summary, although several studies have identified factors contributing to driving performance in PD patients, the relative contribution of motor and cognitive deficits to unsafe driving in this population has yet to be resolved.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Consistent with these latter findings, Madeley et al (1990) found a correlation between PD severity on Webster's rating scale (a 10 item scale of Parkinsonian motor symptoms) and simulated driving reaction time and steering accuracy, and Radford et al (2004) found that the Webster's rating scale, but not cognitive measures, differentiated between safe and unsafe driving on a road test. On the other hand, two more recent studies found that (1) on-road driving performance in PD patients was related to visual processing speed, levodopa dosage, and age, rather than to the Webster's scale (Heikkila et al, 1998); and (2) that although PD drivers were less safe compared to controls on a road test, standard clinical disease markers (i.e., H&Y, UPDRS) did not reliably predict driving performance, suggesting that other measures are necessary to predict driving safety in PD (Wood et al, 2005). In summary, although several studies have identified factors contributing to driving performance in PD patients, the relative contribution of motor and cognitive deficits to unsafe driving in this population has yet to be resolved.…”
Section: Introductionmentioning
confidence: 95%
“…Individuals with Parkinson's disease (PD) may be particularly at increased risk of driving impairment due not only to progressive deterioration in motor functions essential to driving, but also to progressive deterioration in driving-related cognitive functions such as attention, executive control, memory encoding and retrieval, visuoperception, reaction time, and speed of information processing (Heikkila et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…There is a poor correlation between patient questionnaires and disease severity scales in determining medical fitness to drive. 64,65 The cognitive impairment seen in patients with Parkinson's disease includes short term working memory, non-verbal recognition memory, attention and visuospatial deficits. 66,67 Slowness in cognitive functions including processing, choice reaction times, visual perception and memory have been identified as key factors that affect driving in patients with Parkinson's disease.…”
Section: Methods Of Assessmentmentioning
confidence: 99%
“…66,67 Slowness in cognitive functions including processing, choice reaction times, visual perception and memory have been identified as key factors that affect driving in patients with Parkinson's disease. 64 It is important to assess both the motor and cognitive function when performing a medical assessment to determine fitness to drive. Patients with Parkinson's disease may show evidence of reduced power, speed and accuracy of movement.…”
Section: Methods Of Assessmentmentioning
confidence: 99%
“…Thus, six cognitive tests were developed and added to form SMCTests: Complex Attention, Visual Search, Decision-Making, Impulse Control, Planning, and Divided Attention (Innes et al, 2007). Following an evaluation of the literature, deficits in these six cognitive functions were identified as those most frequently identified subjectively during on-road assessments of subjects with brain disorders (e.g., Heikkilä, Turkka, Korpelainen, Kallanranta, & Summala, 1998;Korteling, 1990;Staplin, comprised 20 trials of static images, each containing 70 road-sign stimuli ( Figure 1E). Each screen was presented for a maximum of 10 sec.…”
Section: Apparatusmentioning
confidence: 99%